Potential and limitation of internet of things (IOT) application in the automotive industry: An overview - Ismail, Muhammad Yusri; Beg, M. S.; Jamlos, M. F.; Azmi, W. H.; Badrulhisam, N. H.; Awad, Omar I. (Penerbit Universiti Malaysia Pahang, 2022)
With yearly output exceeding 70 million units, the automotive industry is one of the world's largest manufacturing industries. According to worldwide estimates, the car industry's global revenue was an astounding 3 trillion dollars equating to a combined global GDP of 3.65 percent. The emergence of IoT in the automobile sector has created new opportunities for automakers and purchasers worldwide. With industrial and commercial applications, IoT in the automobile industry has developed into a significant hotspot for a variety of multipurpose applications. From linked automobiles to automated transportation systems, Internet of Things applications have had a significant impact on the worldwide automotive business. The Internet of Things, along with other disruptive technologies, is reshaping the automobile sector as a whole. The evolution of this sector has resulted in the birth of ground-breaking advancements in automobiles, namely linked and autonomous vehicles. Different types of internet of things technology have significant qualities that make them viable candidates as a technology for use in automotive industry. This paper focuses on internet of things latest findings done by previous researcher and describes the operation of the technology. Moreover, this paper also provides insights into some countermeasures against internet of things.